The Impact of Breastfeeding, Complementary Feeding, Immunization History, and Maternal and Child Health on Child Growth - Rayhana, Rayhana; Tamala, Viedya Adhani; Shabariah, Rahmini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The crucial role of parents in providing exclusive breastfeeding, complementary feeding, immunization, and maternal-child health significantly impacts a children's growth. This study aimed to explore the effects of breastfeeding, complementary feeding, immunization history, and maternal-child health on child growth. A quantitative descriptive-analytic study was conducted at the Pengasinan Community Health Center in Bekasi City in 2019, involving 136 mother-child pairs as participants. Data collection utilized questionnaires covering respondent characteristics, breastfeeding and complementary feeding status, basic child immunization, maternal immunization, and the medical history of both mother and child. Data analysis employed chi-square tests using SPSS version 22.0 with a confidence level of 95% and a significance level of P 0.05. Findings revealed that nearly 60% of children exhibited normal growth. Statistical analysis results indicated that exclusive breastfeeding, appropriate complementary feeding, complete basic child immunization, and maternal immunization significantly correlated with normal child growth (p-value 0.05). The implications highlight the urgent need for broader education on the importance of exclusive breastfeeding, appropriate complementary feeding, and complete immunization for both mother and child.